Assistance For Vifas Batik Through Online Promotions, Service Standardization and Customer Database Management - Bria, Lorina; Nuvriasari, Audita (PT FORMOSA CENDEKIA GLOBAL, 2024)
This community service program was carried out at MSME Vifas Batik, Yogyakarta with the general aim of improving business management and performance of MSMEs. Specifically, this activity is aimed at improving the quality of partners' knowledge and skills in terms of online marketing, improving the quality of customer service and utilizing customer databases to market Vifas Batik products. The methods used in this activity are counseling and training, mentoring and monitoring and program evaluation. Based on the results of the activities, it can be recommended that to improve MSMEs business performance, continuous innovation is needed.